A atenção social nos desastres: uma análise sociológica das diversas concepções de atendimento aos grupos sociais afetados - Siena, Mariana (2013)
The disaster is a tragic and critical event that exceeds the everyday life, invaded it, messes it out. It is a phenomenon seen as unacceptable, and that surprises those who are both in and out of the scene; immediate concerns prompt mobilization of resources and exceptional measures, pressing authorities to act quickly (VALENCIO, 2012). Faced with such a phenomenon, civil defense has the institutional mission of coordinating all actions in context, including those of social assistance. However, the national reality tells us that, in Brazilian municipalities, social assistance has a significantly greater institutional presence in relation to civil defense. Howsoever, whether the presence of civil defense, either with the presence of social assistance, public assistance to those social groups affected in the disaster or that enhances their vulnerability to threatening events has been characterized by precariousness. That is, the recurrent has been a kind of care that goal by the kingdom needs (not rights), not exceeding the supply of needs, where is considered enough by the public entity the provision based on mattresses and baskets of food. Studies about politics of civil defense in disaster scenario were made by Valencio (2009, 2012), and Valencio & Valencio (2010). But, there is a gap in the debate about the strategic social care services in the context of disaster. This study aimed to throw light on this gap and analyze the reasons why, in the context of disaster, assistance to vulnerable populations remains as precarious. For this, the main objective of this study was to examine the sociological discourse and practice of social assistance in the context of disaster, using a macro and micro sociological perspective from the case study of the municipality of Ribeirão Preto/SP. Thus, study focused on the ways in which social context portrayed the disaster and, thereafter, identified the affected social groups and individuals from whom made his acting technique. In the present case, the acting technique implemented in the municipality and analyzed in this study was centrally guided in the displacement of a group of residents of some slums, recurrently subject to floods, to the housing complex Toni Wilson Garden.